Sealing ability of MTA, CPM, and MBPc as root-end filling materials: a bacterial leakage study - Paulo Leal MEDEIROS; Norberti BERNARDINELI; Bruno Cavalini CAVENAGO; Sérgio Aparecido TORRES; Marco Antonio Hungaro DUARTE; Clovis Monteiro BRAMANTE; Marina Angélica MARCIANO (University of São Paulo, 2016)
ABSTRACT Objectives To evaluate the sealing ability of three root-end filling materials (white MTA, CPM, and MBPc) using an Enterococcus faecalis leakage model. Material and Methods Seventy single-root extracted human teeth were instrumented and root-ends were resected to prepare 3 mm depth cavities. Root-end preparations were filled with white MTA, CPM, and MBPc cements. Enterococcus faecalis was coronally introduced and the apical portion was immersed in BHI culture medium with phenol red indicator. The bacterial leakage was monitored every 24 h for 4 weeks. The statistical analysis was performed using the Wilcoxon-Gehan test (p<0.05). Results All cements showed bacterial leakage after 24 hours, except for the negative control group. The MBPc showed significantly less bacterial leakage compared with the MTA group (p<0.05). No significant differences were found between the CPM and the other groups. Conclusions The epoxy resin-based cement MBPc had lower bacterial leakage compared with the calcium silicate-based cements MTA and CPM.